2018
DOI: 10.1039/c8ta05798b
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced suppression of the miscibility gap in nanostructured Mg2Si–Mg2Sn solid solutions

Abstract: Strain-induced suppression of the miscibility gap in solid solutions of Mg2Si and Mg2Sn was studied to reduce lattice thermal conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 46 publications
4
46
5
Order By: Relevance
“…Recently, the present authors and collaborators investigated the effect of non-equilibrium processing on the microstructure evolution (and transport properties) in the Mg 2 Si 0.7 Sn 0.3 system and found that instead of phase-separating, the system tended to form a solidsolution with superior TE performance, contrary to expectations and prior works [56,65]. This was ascribed to (elastic) coherency effects and was verified via quantitative multi-physics phase field simulations [39].…”
Section: Nanostructured Thermoelectric Materialsmentioning
confidence: 62%
See 4 more Smart Citations
“…Recently, the present authors and collaborators investigated the effect of non-equilibrium processing on the microstructure evolution (and transport properties) in the Mg 2 Si 0.7 Sn 0.3 system and found that instead of phase-separating, the system tended to form a solidsolution with superior TE performance, contrary to expectations and prior works [56,65]. This was ascribed to (elastic) coherency effects and was verified via quantitative multi-physics phase field simulations [39].…”
Section: Nanostructured Thermoelectric Materialsmentioning
confidence: 62%
“…Many of these approaches have been inspired by metallurgy and thus the time is ripe to translate much of what has been learned on ICME-enabling microstructure-sensitive (structural) alloy design to the problem of designing (self-assembled) TE microstructures for optimal performance. While the modeling framework via PFM has shown to result in (semi-)quantitative predictions that compare well with experiments [39], a robust ICME research program on microstructure design of TE materials requires reliable and efficient UQ/UP frameworks. Figure 2 illustrates an schematic phase diagram in which the material shows an inherent instability in certain regions of the composition space.…”
Section: Nanostructured Thermoelectric Materialsmentioning
confidence: 98%
See 3 more Smart Citations